PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA JASA SYNAILS ART KABUPATEN BEKASI - Raymond Peres Loi; M. Fadhli Nursal; Neng Siti Komariah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of Service Quality and Price on Customer Satisfaction, both partially and simultaneously. The population in this study consisted of all customers who had used the services of Synails Art, located in Pondok Tanah Mas, Jalan Bosih Raya, Cibitung District. The sample was determined using the purposive sampling technique, resulting in a total of 97 respondents. The results of the study indicate that Service Quality and Price have a significant influence on Customer Satisfaction at Synails Art. This is evidenced by the multiple linear regression equation, namely Y = 4.729 + 0.164X₁ + 0.532X₂. Based on the results of the simultaneous test (F-test), both independent variables were proven to have a significant influence on Customer Satisfaction, as indicated by the calculated F-value of 93.481, which is greater than the F-table value of 3.09. Meanwhile, the results of the partial test (t-test) show that the Service Quality variable has a positive and significant influence on Customer Satisfaction, with a calculated t-value of 2.174 > the t-table value of 1.986 and a significance value of 0.03 < 0.05. The Price variable was also proven to have a positive and significant influence on Customer Satisfaction, with a calculated t-value of 7.820 > the t-table value of 1.986 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.658 indicates that Service Quality and Price are able to explain 65.8% of the variation in Customer Satisfaction, while the remaining 34.2% is influenced by other factors not discussed in this study.